A Systematic Review and Provisional Metanalysis on Psychopathologic Burden on Health Care Workers of Coronavirus Outbreaks - Galli, Federica; Pozzi, Gino; Ruggiero, Fabiana; Mameli, Francesca; Cavicchioli, Marco; Barbieri, Sergio; Canevini, Maria Paola; Priori, Alberto; Pravettoni, Gabriella; Sani, Gabriele; Ferrucci, Roberta (Frontiers in Psychiatry, 2020)
Background. The new coronavirus (SARS-CoV-2) shows several similarities with previous outbreaks of Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS). Aim of this systematic review and meta-analysis is to provide evidence of the psychopathologic burden on health care workers (HCWs) of the first two deadly coronavirus outbreaks to get lessons for managing the current burden of COVID-19 outbreak. Method. According to Cochrane Collaboration guidelines and the PRISMA Statement, the study quantified the effects of frontline work on mental health of HCWs. Major databases were searched for observational and case-control studies evaluating mental health indexes reported by front-line work. This study computed the percentage of sample that reported clinically significant levels of psychiatric symptoms. Cohen’s d was used for comparing mental health outcomes of HCWs directly involved in addressing pandemic emergency with a control group that was not directly exposed to such conditions. Pooled effect sizes (dw) were estimated whenever at least three independent studies yielded data. Heterogeneity of findings and bias of publication were also estimated. Findings. Fifteen studies have been selected for a total of 7393 HCWs. From 9.6 to 51% of HCWs reported symptoms of Post-Traumatic Stress Disorder (PTSD) and from 20 to 75% reported psychiatric symptoms, with a prevalence of anxiety and depression. From one to the three years after outbreak, from 2 to 19% reported PTSD symptoms and from 5 to 90% psychiatric symptoms. Interestingly, HWCs who were directly involved in pandemic emergency showed higher depressive and anxious symptoms (dw=.66 (.46-.85); p<.001) than ones who were not directly exposed. Similarly, the direct involvement significantly affected the severity of PTSD symptoms (dw = .30 (.21 - .39); p < .001). Conclusion. Health care professionals in general and most of all for frontline workers are at risk of psychiatric outcome following outbreaks and for at least three years later. Mental health interventions for professionals exposed to COVID-19 need to be immediately implemented. Further studies are warranted to investigate long-term consequences carefully, and to look for mediating and buffering factors as well. The role of clinical psychologists and psychiatrists in delivering adequate interventions is critically important.